Domestic Groundwater Depletion Supports China's Full Supply Chains. Issue 5 (17th May 2022) - Sun, Siao; Tang, Qiuhong; Konar, Megan; Huang, Zhongwei; Gleeson, Tom; Ma, Ting; Fang, Chuanglin; Cai, Ximing
Abstract: Groundwater use underpins much economic production. The unsustainable use of groundwater threatens environmental flows in surface waters, sustainable development, and future food security. The connection between agricultural trade and groundwater depletion has been recently highlighted, but how groundwater depletion supports the production of industrial and tertiary goods, trade, and consumption remains less well understood. Here, we present the first analysis of groundwater use and depletion embedded in the complete supply chain of China (including primary, secondary, and tertiary products). We use a multiregion input‐output analysis coupled with the high‐resolution groundwater use modeling to track groundwater depletion from production to end consumer. Our modeling results show that groundwater depletion occurred primarily in water scarce North China for agricultural production, but the depleted resource was then incorporated throughout the supply chain and dispersed across Chinese and international consumers. ∼64 billion m 3 yr −1 (±1 billion m 3 yr −1 ) groundwater was depleted in China, in which more than a half was from Xinjiang, Hebei, Henan and Heilongjiang Provinces. Approximately 40% of the groundwater depletion can be traced to interprovincial transfer (21 billion m 3 yr −1 ) and export (4.8 billion m 3 yr −1 ). The hot spots for final consumption of groundwater depletion were major cities in both North and South China. Importantly, over 60% of the groundwater depletion was embodied in industrial and tertiary products for final consumption, highlighting the importance of tracing groundwater through the full economy. Groundwater depletion represents a long‐term risk to supply chains, and policy‐makers can use this understanding to sustainably manage groundwater and diversify supply chains. Plain Language Summary: Groundwater is a critical resource that is under increased pressure due to unsustainable exploitation. Groundwater resources underpin both national supply chains and global trade, but how groundwater supports the full supply chain of a nation remains unresolved. This study traces the groundwater depletion incorporated in the complete supply chain (including industrial and tertiary products, not just primary goods) of China through interprovincial transfers and international exports. The results show how groundwater depletion, which is concentrated in North China, is distributed to domestic and international consumers of final goods. International importers receive China's groundwater in the receipt of industrial products. We highlight that groundwater depletion represents a long‐term risk to supply chains. Key Points: Groundwater depletion is traced using a multi‐region input‐output analysis coupled with the high‐resolution groundwater use modeling About 21 billion m 3 yr −1 groundwater depletion, primarily from water scarce Northern‐China, is virtually transferred domestically Groundwater depletion supporting export to the Rest of the World is estimated to be 4.8 billion m 3 yr −1